MANAJEMEN ZAKAT: MASA NABI MUHAMMAD SAW DAN SAHABAT KHULLAFAURRASYIDIN - Rahmad, Rahmad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
Apart from being a religious service, Zakat also contains social and economic values. However, inappropriate management individually only realizes the value of worship. The behavior of zakat management carried out by the Prophet Muhammad SAW and Friends of Khullafaurrasyidin can be used as a reference that government involvement is needed so that zakat management can run optimally, so that one of the functions of zakat, namely empowering mustahik to become muzakki, can be realized and the zakat surplus target can be realized